2015
DOI: 10.2217/pmt.15.19
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in the Development of Chemotherapy-Induced Neuropathy

Abstract: SUMMARY Chemotherapy-induced peripheral neuropathy (CIPN) is a debilitating and painful condition seen in patients undergoing treatment with common agents such as vincristine, paclitaxel, oxaliplatin and bortezomib. The mechanisms of this condition are diverse, and include an array of molecular and cellular contributions. Current research implicates genetic predispositions to this condition, which then may influence cellular responses to chemotherapy. Processes found to be influenced during CIPN include increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 129 publications
(142 reference statements)
5
117
0
4
Order By: Relevance
“…These effects can negatively influence neuronal and glial cell phenotypes which may contribute to the development of CIPN, thus hindering the understanding of specific mechanism underlying this side effect. [4] A recent review by Boyette-Davis et al . [4] identified a number of different mechanisms of actions for CIPN [Table 1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects can negatively influence neuronal and glial cell phenotypes which may contribute to the development of CIPN, thus hindering the understanding of specific mechanism underlying this side effect. [4] A recent review by Boyette-Davis et al . [4] identified a number of different mechanisms of actions for CIPN [Table 1].…”
Section: Resultsmentioning
confidence: 99%
“…[4] A recent review by Boyette-Davis et al . [4] identified a number of different mechanisms of actions for CIPN [Table 1]. …”
Section: Resultsmentioning
confidence: 99%
“…24,[49][50][51][52] Exercise may ameliorate treatment-related or stressrelated chronic inflammation, 53,54 oxidative stress, 55,56 impaired neurotransmission, 57,58 or cytokine and hormonal derangements. Yet our results suggest that even small amounts of vigorous exercise may ameliorate these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data revealed that chemotherapy agents, such as oxaliplatin , vincristine , paclitaxel and bortezomib , are a significant cause of peripheral neuropathy (as reviewed by Boyette‐Davis et al . ). Although the mechanisms underlying this effect are poorly understood, chemotherapeutics were found to alter Na V s activity by mobilizing intraneuronal calcium .…”
Section: Exogenous Triggersmentioning
confidence: 97%